Relationship between Teacher Competence (Coach) and Improvement of Extracurricular Participants' Singing Ability - Avelya Wedyan, Sherina; Hadi, Harisnal (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to determine students' interest in extracurricular singing at SMP Negeri 3 Lubuk Sikaping and what factors influence students' interest in participating in extracurricular singing activities at SMP Negeri 3 Lubuk Sikaping. The research method applied in this study is a descriptive approach in the form of qualitative research. The tool used in this research is the researcher himself who is actively involved in making direct observations in the field as the main method for collecting data. The data used consisted of primary and secondary data, which were collected through observation, interviews, literature study, and document collection. The data analysis process involved the clarification and summarisation stages. The research findings show that the implementation of extracurricular singing at SMP Negeri 3 Lubuk Sikaping which is carried out for the readiness of singing competitions such as FLS2N and other singing competitions has been successfully implemented well, but there are several obstacles in its implementation that are not in accordance with the activity programme so that extracurricular implementation is still less effective. In terms of the approach applied, teachers have chosen methods that are suitable for the content of the material. However, because the cultural arts teacher is a teacher who is not competent in the field of music. So that during the implementation of extracurricular singing the teacher is less able to know the technique of singing. Students who follow are less serious when extracurricular activities take place. Therefore, the achievement of the success rate in the implementation of extracurricular singing activities at SMP Negeri 3 Lubuk Sikaping has not been achieved.